Lower Masticatory Performance Is a Risk for the Development of the Metabolic Syndrome: The Suita Study - Fushida, Shuri; Kosaka, Takayuki; Nakai, Michikazu; Kida, Momoyo; Nokubi, Takashi; Kokubo, Yoshihiro; Watanabe, Makoto; Miyamoto, Yoshihiro; Ono, Takahiro; Ikebe, Kazunori (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Declined masticatory function has recently been receiving attention as a risk factor for poor general health. The present longitudinal analysis was conducted to clarify the relationship between decreased masticatory performance and the development of the metabolic syndrome (MetS) in a general urban cohort in Japan. Methods: We surveyed 599 participants (254 men, 345 women; mean age at baseline, 65.8±7.8 years) who underwent physical health checkups in the Suita study. We evaluated masticatory performance at baseline using test gummy jelly and divided participants into two groups: a “Lower group,” comprising participants in the lower 25% of the masticatory performance at baseline; and a “Normal group,” comprising all others. We estimated hazard ratios (HRs) for the Lower group by using Cox proportional hazard regression analysis to develop the MetS and the components of the MetS at follow-up, adjusting for age, smoking status, and periodontal status. Results: On Cox proportional hazard regression analysis, the multivariable adjusted hazard ratio for the development of the MetS in the Lower group was 2.24 (95% confidence interval, 1.12-4.50) in men. The multivariable adjusted hazard ratio for the development of high blood pressure was 3.12 (1.42–6.87), for high triglycerides was 2.82 (1.18–6.76), and for high fasting plasma glucose was 2.65 (1.00–7.00) in men. Conclusions: Lower masticatory performance suggested to be a risk factor for the development of the MetS as well as MetS components such as high blood pressure, high triglycerides, and high fasting plasma glucose in Japanese men.